Prospects of the world rubber industry in the new decade - Budiman A F S (Proceedings : Indonesian Rubber Conference and IRRDB symposiun 2000 Indonesian Rubber Research Institute, Bogor, Indonesia, 12-14 September 2000.V.1.pp.7-15.)
We have seen the rubber industry undergoing many changes in the past decade and now foresee further changes as we enter this new decade. We are quite aware that rubber, or technically, known as elastomer, have been indispensable in our daily life. Nowadays, we cannot imagine a day without tyres on the cars, buses, trucks, airplanes and farm vehicles. Less visibly, automotive vehicles contain hundreds of large and small elastomer components, and even more so with mining and industrial machinery such as transmission and conveyor belts, engine mountings, gaskets and seals, etc. Not the least, we are living with a myriad of rubber products in our house and kitchen, garden, sporting ground and hospitals. Elastomers is considered a minor member in the world of construction materials. Compared to metals, wood, ceramics, plastics and fibres, quantity-wise elastomers are the smallest, their existence very much taken for granted although their importance should not be discounted. As a daily user of rubber products, we tend no to bother where from the bouncy and springy material are sourced, whether from trees or petroleum. Actually the total elastomers consumed worldwide are roughly 39;Natural and 61;Synthetics. In rubber articles, the two kinds of elastomers are never distinguished by us as users. In fact, they are either natural, synthetic or blends of the two in different proportions. The maker of these articles are basically picking the kinds of rubber to be used on the grounds of technological merits and economic availability. As such, natural rubber has a unique position among agricultural commodities by the fact that it is essentially an industrial raw material. The largest consumers of natural(and also synthetic) rubber is the pneumatic tyre. Actually there are hundreds of rubber articles in use, but why tyres in particular? It is simply because tyres wear-off during usage whereas most of the other rubber articles are relatively long lasting. The rubber part of the tyre is eaten by the road it rolls on, therefore it needs replacement after certain mileage. Due to their special properties, over 70;of natural rubber and 60;of synthetic usage is in the manufacture of pneumatic tyres. No wonder the first natural rubber plantations and synthetic rubber plants were built by the major tyre producres. It is very interesting to note that the two kinds of rubbers have been used together symbiotically while their origins are a world apart. Natural rubber is derived from hevea trees that grow very well in tropical soil and climate. Rubber cultivation has been viewed as a source of foreign exchange earner of developing countries, and more recently also as an important source of emplyoment opportunity and daily income for the rapidly growing population of these countries. Synthetic rubber originates from scientific curiosity of the relationship between chemical structure and physical properties of natural rubber, resulting in the man-made creation of natural rubber imitations but later-on developed into a rich array of materials obtained by polymerization process of monomers, all tailor-made to achieve specific properties. The monomers can be derived from petroleum, coal and alcohol, but today they are almost invariably produced from petroleum fractions. The major bulk monomers are butadiene and styrene, the basic ingredients to yield the two dominant bulk synthetic rubbers, namely the SBR (styrene-butadiene-rubber) and PBR (cis-polybutadiene rubber). According to IISRP (1999), the current world elastomer consumption totalling around 17 million tons per year consists of 38;NR, 20;SBR (solid), 14;SBR (latex), 12;PBR, 5;EPDM, 2;chloroprene, 2;nitrile and 7;synthetics. Thus in terms of quantity, NR is still largest.
Keywords: World rubber industry